Iron Status in Early Infancy Is Associated With Attentional Flexibility and Cognitive Achievement in Rural Gambia. (7th June 2021) - McCann, Sam; Mbye, Ebrima; Touray, Ebou; Ceesay, Muhammed; Acolatse, Lena; Milosavljevic, Bosiljka; Mason, Luke; Johnson, William; Okot, Patrick; Colley, Alhassan; Janneh, Abubacarr; Lloyd-Fox, Sarah; et al.
Abstract: Objectives: To determine the relationship between iron status in early infancy (1–5 months) and longitudinal trajectories of cognitive development (5–18 months) in a cohort of infants from rural Gambia. Methods: This study used data from the Brain Imaging for Global Health (BRIGHT) study, which recruited pregnant women (n = 223) and followed up mothers and their children to 18 months of age (n = 191). Infant blood samples collected at 1 and 5 months of age were analysed for soluble transferrin receptor (sTfR) and ferritin using a COBAS INTEGRA 400 (Roche). Cognitive development was measured at 5, 8, 12 and 18 months of age using the Mullen Scales of Early Learning (MSEL) and an eye tracking measure of attentional flexibility (disengagement time). For each outcome measure, mixed effects models of individual developmental trajectories from 5–18 months of age were developed. Each model had a different measure of iron status as the primary exposure (ferritin or sTfR at 1 or 5 months of age) and was adjusted for confounding factors. Results: Prevalence of iron deficiency (ferritin < 12μg/L or < 30 μg/L if CRP > 5mg/L) increased from 0% to 29.5% between 1 and 5 months of age. In mixed effects models, a -1mg/L difference in sTfR (indicating better iron status) at 1 month of age was associated as with a 31.2ms difference in disengagement time (SE = 13.1, p = 0.017) at each time point from 5–18 months of age, but was not associated with MSEL developmental trajectory. A -1mg/L difference in sTfR at 5 months of age associated with a 0.6 point difference in MSEL score from 5–18 months of age (SE = 0.180, p = 0.001) and a 10.6ms difference in disengagement time (SE = 4.8, p = 0.028) across the same period. There was no relationship between ferritin concentration at 1 or 5 months and trajectories of either MSEL or disengagement time (all p > 0.05). Conclusions:  Infants under 6 months of age in rural Gambia are at risk of iron deficiency. Poor iron status in early infancy, measured by sTfR but not ferritin, is associated with both global cognition and a specific measure of attentional flexibility, from 5–18 months of age. Maintenance of adequate iron in infants up to 6 months of age may benefit the developing brain. Funding Sources: Bill and Melinda Gates Foundation and Medical Research Council (UK).